2019
DOI: 10.1177/2057158519845321
|View full text |Cite
|
Sign up to set email alerts
|

Nurse professional competence (NPC) assessed among newly graduated nurses in higher educational institutions in Europe

Abstract: Nursing education will play an important role in further advancing healthcare transformation in the future. The aim of this study was to assess and compare nursing education and self-reported professional competence among nursing students graduating with a bachelor's degree from higher education institutions in Europe. Data were collected using the Nurse Professional Competence Scale including 88 items and eight competence areas. In total, 752 nursing students at 11 higher education institutions in Europe part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 12 publications
7
50
3
Order By: Relevance
“…Taking time to reflect is a dynamic process that involves gaining new perspectives to develop nursing (Davis, Taylor, & Reyes, 2014). In relation to competence development and lifelong learning, the results in this study show the importance of self‐reflection as a way to further develop oneself, and this has also been shown in other studies (Forsman et al., 2019; Nilsson et al., 2019). Yet, the ability to think critically decreased after 9–15 months of clinical practice among NGRNs (Willman et al., 2020b).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Taking time to reflect is a dynamic process that involves gaining new perspectives to develop nursing (Davis, Taylor, & Reyes, 2014). In relation to competence development and lifelong learning, the results in this study show the importance of self‐reflection as a way to further develop oneself, and this has also been shown in other studies (Forsman et al., 2019; Nilsson et al., 2019). Yet, the ability to think critically decreased after 9–15 months of clinical practice among NGRNs (Willman et al., 2020b).…”
Section: Discussionsupporting
confidence: 87%
“…The results show that the NGRNs' experiences challenge in the leadership and organisation of nursing care in complex patient situations. This is an important finding, and other recent statements (WHO, 2020) and studies presenting results on NGRNs' professional competence (Gardulf et al., 2019; Halabi, Lepp, & Nilsson, 2020; Nilsson et al., 2019) indicate a need to transform nursing education so it has a greater focus on competencies relating to leadership and the organisation of nursing care. These competencies are often taught during the latter part of nursing education programmes (Theander et al., 2016), which will not give nursing students the possibility to internalise theory and practice.…”
Section: Discussionmentioning
confidence: 59%
“…Previous studies using the NPC Scale reported good reliability in terms of Cronbach’s alpha ranging from 0.71 to 0.96 in samples of newly graduated nurses in Sweden (Forsman et al, 2020; Nilsson et al, 2014; Nilsson et al, 2018) and in Europe (Nilsson et al, 2019). The scale has shown that it can be used to evaluate the outcomes of nursing education programs (Castrèn et al, 2017; Theander et al, 2016), and could be used to assess nurses’ competences in relation to the needs in health care organizations, to identify self-reported competences and in tailoring introduction programs for newly employed nurses (Nilsson et al, 2014).…”
Section: Methodsmentioning
confidence: 97%
“…This study suggests that nursing exchange programmes increase knowledge on global health and global nursing as indicated in other studies (34)(35)(36). Nursing curricula should also include global health to prepare nurses for the needs of the global community (37), such as the SRCUC who has adopted global nursing as their pro le area.…”
Section: Global Perspectivesmentioning
confidence: 61%